Multidrug-resistant HIV viral rebound during early syphilis: a case report - Giacomelli, Andrea; Micheli, Valeria; Cattaneo, Dario; Mancon, Alessandro; Gervasoni, Cristina (BMC infectious diseases, 2020)
Background Syphilis has been associated with an increase in HIV RNA and a temporary decline in CD4 T cell counts in people living with HIV who are not receiving antiretroviral treatment (ART), and may be associated with a transient HIV RNA rebound in those who are receiving ART. Our case is the first to highlight the risk of a multidrug-resistant HIV viral rebound during the course of early syphilis even if antiretroviral drug concentrations are within the therapeutic range. Case presentation This 50-year-old HIV-1-positive male patient with concomitant early syphilis presented with an HIV RNA rebound (8908 copies/mL) during a scheduled visit to our clinic. He was receiving a stable ART regimen consisting of darunavir/cobicistat plus dolutegravir, and had a 15-year history of viral suppression. Good short-term drug adherence could be inferred as liquid chromatography tandem mass spectrometry showed that his trough antiretroviral drug concentrations were within the therapeutic range: darunavir 2353 ng/mL (minimum effective concentration > 500 ng/mL) and dolutegravir 986 ng/mL (minimum effective concentration > 100 ng/mL). A plasma RNA genotype resistance test revealed wild-type virus in the integrase region and protease region (PR), but extensive resistance in the reverse transcriptase (RT) region (M41L, E44D, D67N, K70R, M184V, L210W and T215Y). Phylogenetic analysis of next-generation sequences (used to investigate the presence of minor viral variants), the PR and RT sequences from plasma HIV RNA and pro-viral DNA extracted from peripheral blood mononuclear cells during the viral rebound, and a Sanger sequence obtained during a previous virological failure suggested clonal viral expression because the previous PR resistance mutations had been lost or had not been archived in pro-viral DNA. Conclusions This case shows that early syphilis may cause an HIV RNA rebound in patients under stable virological control with the potential of transmitting an extensively drug-resistant virus.